Respuesta :
Answer:
x = 0
Step-by-step explanation:
Hello!
2(x + 4) - 5 = 3x + 3
Distribute the 2
2x + 8 - 5 = 3x + 3
Combine like terms
2x + 3 = 3x + 3
Subtract both sides by 2x
3 = x + 3
Subtract both sides by 3
0 = x
The answer is x = 0
Hope this helps!
Answer: [tex]x=0[/tex]
Simplify both sides of the equation
[tex]2(x-4)-5=3x+3\\(2)(x)+(2)(4)+-5=3x+3(Distribute)\\2x+8+-5=3x+3[/tex]
[tex](2x)+(8+-5)=3x+3[/tex](Combine Like Terms)
[tex]2x+3=3x+3[/tex]
Subtract 3x from both sides
[tex]2x+3-3x=3x+3-3x\\-x+3=3[/tex]
Subtract 3 from both sides
[tex]-x+3-3=3-3\\-x=0[/tex]
Divide both sides by -1
[tex]-x/1=0/-1\\x=0[/tex]